2018
DOI: 10.2298/jsc171109043h
|View full text |Cite
|
Sign up to set email alerts
|

Effect of structure on extraction behavior of praseodymium with a series of unsymmetrical diglycolamides from hydrochloric acid

Abstract: The extraction behavior of Pr(III) has been investigated using four kinds of unsymmetrical diglycolamide (DGA) extractants having different alkyl chain lengths, namely N,The effect of the alkyl chain of amidic N atoms in DGAs on the extraction ability of Pr(III) is discussed. The extraction of hydrochloric acid and Pr(III) from hydrochloric acid medium by DGAs in sulfonated kerosene, toluene and octanol was studied. The effect of extractant concentration and diluents on the distribution ratio (D) of Pr(III) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 27 publications
2
1
0
Order By: Relevance
“…Han et al demonstrated that the N , N ′-di­( n -dodecyl) DGAs with smaller N , N ′-alkyl substituents are beneficial to praseodymium­(III) extraction and follow the trend methyl > ethyl > propyl > butyl . We observe the same overall trend in our series of extracting agents 3 , 7 , and 8 ; that is, the extraction strength increases with shortening of the alkyl substituent (Figures c and a).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Han et al demonstrated that the N , N ′-di­( n -dodecyl) DGAs with smaller N , N ′-alkyl substituents are beneficial to praseodymium­(III) extraction and follow the trend methyl > ethyl > propyl > butyl . We observe the same overall trend in our series of extracting agents 3 , 7 , and 8 ; that is, the extraction strength increases with shortening of the alkyl substituent (Figures c and a).…”
Section: Resultssupporting
confidence: 93%
“…Han et al demonstrated that the N,N′-di(n-dodecyl) DGAs with smaller N,N′-alkyl substituents are beneficial to praseodymium(III) extraction and follow the trend methyl > ethyl > propyl > butyl. 36 We observe the same overall trend in our series of extracting agents 3, 7, and 8; that is, the extraction strength increases with shortening of the alkyl substituent (Figures 4c and 5a). Interestingly, this effect is only pronounced in the early lanthanide region (from lanthanum to samarium) because all three extractants show comparable D for europium through lutetium.…”
Section: ■ Results and Discussionsupporting
confidence: 76%
See 1 more Smart Citation